2023
DOI: 10.1158/2767-9764.crc-22-0427
|View full text |Cite
|
Sign up to set email alerts
|

Metronomic Administration of Topotecan Alone and in Combination with Docetaxel Inhibits Epithelial–mesenchymal Transition in Aggressive Variant Prostate Cancers

Taraswi Mitra Ghosh,
Suman Mazumder,
Joshua Davis
et al.

Abstract: Prostate cancer (PCa) is the second leading cause of non-cutaneous cancer-related deaths in American men. Androgen deprivation therapy (ADT), radical prostatectomy, and radiation therapy remain the primary treatment for early-stage PCa patients (castration-sensitive: CSPC). Following ADT, many patients ultimately develop metastatic castration-resistant PCa (mCRPC). Standard chemotherapy options for CRPC are Docetaxel (DTX) and Cabazitaxel (CBZ), which increase median survival, although the development of resis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In addition, the metronomic application of several chemotherapeutics has been found to inhibit the EMT process in cancer cells 75 , 76 . Single-cell RNA-seq and RNA-seq analysis have indicated that metronomic topotecan treatment induced the downregulation of EMT markers, including CD55 and HAS3, in metastatic castration-resistant prostate cancer 76 .…”
Section: Mechanisms and Rationale Of Mctmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the metronomic application of several chemotherapeutics has been found to inhibit the EMT process in cancer cells 75 , 76 . Single-cell RNA-seq and RNA-seq analysis have indicated that metronomic topotecan treatment induced the downregulation of EMT markers, including CD55 and HAS3, in metastatic castration-resistant prostate cancer 76 .…”
Section: Mechanisms and Rationale Of Mctmentioning
confidence: 99%
“…In addition, the metronomic application of several chemotherapeutics has been found to inhibit the EMT process in cancer cells 75 , 76 . Single-cell RNA-seq and RNA-seq analysis have indicated that metronomic topotecan treatment induced the downregulation of EMT markers, including CD55 and HAS3, in metastatic castration-resistant prostate cancer 76 . A preclinical study revealed that metronomic cordycepin upregulated E-cadherin and downregulated N-cadherin protein expression in a human oral squamous cell carcinoma xenograft model, which suggests the EMT process was inhibited 75 .…”
Section: Mechanisms and Rationale Of Mctmentioning
confidence: 99%
“…Consequently, researchers have developed selective inhibitors for both TOPO I and TOPO II, which have been employed in treating various cancers. For instance, FDA-approved TOPO I inhibitors camptothecin and topotecan decreased the colon, lung, prostate, and melanoma cancer cell development both in in vitro and in clinical trials. Additionally, TOPO II inhibitors such as etoposide and doxorubicin, also approved by the FDA, are currently used for lung, breast, ovarian, and prostate cancer treatment. Although selective topoisomerase inhibitors are effective in decreasing prostate cancer cell progression, the compounds have several side effects including hematological toxicity, diarrhea, and neutropenia . Moreover, inhibiting one type of topoisomerase might inadvertently enhance the activity of the other, leading to drug resistance. , Regarding this, dual inhibition of both TOPO I and TOPO II has emerged as a promising strategy to counter the simultaneous increase in topoisomerase activity and to prevent drug resistance.…”
Section: Introductionmentioning
confidence: 99%